Characterization of alumina foam prepared by space holder method - Abdullah, Noorhanis Nazuwa; Mat Noor, Fazimah (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Ceramic foams can be categorized as brittle and porous and composed of many pores inside compared to other metals and polymers. Due to their unique properties, ceramic foams have been widely used in various applications such as thermal insulation, filtration and biomedical implants. In this research, the ceramic foam which is alumina foam was fabricated through the space holder method. The raw materials used were alumina powders, Carboxymethyl cellulose (CMC) and Polyethylene glycol (PEG) as binders and coconut husk (CH) powder as space holder materials. The coconut husk powder varied in the different compositions of 0, 5, 10, 15, 20 and 25 wt %. CMC and PEG binders act as a glue that attaches all the raw materials resulting in a strength increase of alumina green samples during compaction. All the raw materials were then mixed, ball-milled and compacted into a solid cylinder sample of 0.7 cm in height. Next, the alumina green samples were sintered at a temperature of 1350 ˚C in an electrical box furnace. Several types of tests were also conducted to analyse the physical and mechanical properties of alumina foams that were fabricated with different coconut husk powder compositions. Microstructure observation using Scanning Electron Microscope (SEM) was conducted that shows the alumina foams have single and interconnected open pores with pore sizes in the range of 2 to 100 μm. From the results, it was found that the density decreased, and the porosity increased in the range of from 1.7936 to 1.4781 g/cm3 and 36.16 to 57.66% respectively. As the density decreased, the compressive strengths were found to decrease from 1.45853 to 0.35174 N/mm2. From the data obtained, the alumina foam that was fabricated by coconut husk powder as a space holder material is suitable for filtration applications such as molten metal and automobile exhaust gas filtration.